Temperature Driven Unusual Reversible p‐ to n‐Type Conduction Switching in Bi2Te2.7Se0.3. Issue 7 (23rd April 2019) - Bohra, Anil K.; Ahmad, Sajid; Bhatt, Ranu; Singh, Ajay; Bhattacharya, Shovit; Basu, Ranita; Sarkar, Pritam; Meshram, Kailash N.; Debnath, Anil K.; Bhatt, Pramod; Sarkar, Shaibal K.; Patro, P. K.; et al.
Abstract : Bismuth telluride based alloys are electronic semiconductors, which exhibit n‐ or p‐type conduction due to the formation of Te vacancies or antisite defects, i.e., substitution of Bi on Te site or vice versa. Here, it is demonstrated that the temperature dependent Seebeck coefficient of Bi2 Te2.7 Se0.3 exhibits a reversible change in conduction from p‐ to n‐type at temperatures >487 K without exhibiting any structural transformation. The detailed characterization revealed that conversion of BiTe/Se antisite defects into Te vacancies is responsible for the p–n transition. The observed p–n transition makes Bi2 Te2.7 Se0.3 an ideal candidate for temperature controlled electronic switches. Abstract : Bismuth telluride based alloys usually exhibit n‐ or p‐type conduction due to Te vacancies or due to the formation of Bi vacancies or anitisite defects, i.e., Bi substitution on Te sites or vice versa. The temperature dependent Seebeck coefficient of Bi2 Te2.7 Se0.3 exhibits a reversible change in conduction from p‐ to n‐type at temperatures >487 K without exhibiting any structural transformation. The conversion of BiTe/Se antisite defects into Te vacancies is responsible for p to n transition of Bi2 Te2.7 Se0.3 .